Influence of Yersinia pseudotuberculosis outer proteins (Yops) on interleukin-12, tumor necrosis factor alpha and nitric oxide production by peritoneal macrophages - Monnazzi, LGS; Carlos, Iracilda Zeppone [UNESP]; de Medeiros, BMM (Elsevier B.V., 2004)
An essential key to pathogenicity in Yersinia is the presence of a 70 kb plasmid (pYV) which encodes a type-III secretion system and several virulence outer proteins whose main function is to enable the bacteria to survive in the host. Thus, a specific immune response is needed in which cytokines are engaged. The aim of this study was to assess the influence of Yersinia outer proteins (Yops) released by Yersinia pseudotuberculosis on the production of the proinflammatory cytokines, interleukin-12 (IL-12), and tumor necrosis factor alpha (TNF-alpha), and nitric oxide (NO) by murine peritoneal macrophages. To this end, female Swiss mice were infected intravenously with wild-type Y pseudotuberculosis or with mutant strains unable to secrete specific Yops (YopE, YopH, YopJ, YopM, and YpkA). on the 7th, 14th, 21st, and 28th days after infection, the animals were sacrificed and the cytokines and NO were assayed in the peritoneal macrophages culture supernatants. A fall in NO production was observed during the course of infection with all the strains tested, though during the infection with the strains that did not secrete YopE and YopH, the suppression occurred later. There was, in general, an unchanged or sometimes increased production of TNF-alpha between the 7th and the 21st day after infection, compared to the control group, followed by an abrupt decrease on the last day of infection. The IL-12 production was also suppressed during the infection, with most of the strains tested, except with those that did not secrete YopJ and YopE. The results suggest that Yops may suppress IL-12, TNF-alpha, and NO production and that the most important proteins involved in this suppression are YopE and YopH. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Yersinia pseudotuberculosis; interleukin-12; tumor necrosis factor alpha; nitric oxide; Yops